Desflurane protects against liver ischemia/reperfusion injury via regulating miR-135b-5p. Issue 1 (7th September 2020) - Zhong, Mengxia; Che, Lei; Du, Meiqing; Liu, Ke; Wang, Dalong
Abstract : Background: A number of anesthetics have protective effect against ischemia-reperfusion (I/R) injury, including desflurane. But the function and molecular mechanism of desflurane in liver I/R injury have not been fully understood. The aim of this study was to investigate the effect of desflurane on liver I/R injury and further investigated the molecular mechanisms involving in miR-135b-5p. Methods: The models of liver I/R injury in rats were established, and received desflurane treatment throughout the injury. Serum alanine transaminase (ALT) and aspartate transaminase (AST) were measured and compared between groups. H/R-induced cell model in L02 was established, and were treated with desflurane before hypoxia. Quantitative real-time polymerase chain reaction was performed to determine the expression of miR-135b-5p in different groups. The cell apoptosis was detected using flow cytometry assay. Western blot was used for the measurement of protein levels. Results: I/R significantly increased serum levels of ALT and AST in rats, which were reversed by desflurane treatment. Desflurane also significantly attenuated the increase of cell apoptosis induced by I/R in both vivo and vitro . MiR-135b-5p significantly reversed the protective effect of desflurane against liver I/R injury. Additionally, Janus protein tyrosine kinase (JAK)2 was shown to be a target gene of miR-135b-5p, and miR-135b-5p overexpression significantly decreased the protein levels of p-JAK2, JAK2, p-STAT3. Conclusion: Desflurane attenuated liver I/R injury through regulating miR-135b-5p, and JAK2 was the target gene of mIR-135b-5p. These findings provide references for further development of therapeutic strategies in liver injury.